Kathy Martin (doctoral student) and Sue Stephenson (field assistant) at La Perouse Bay - Bazely, Dawn R. (1983)
Kathy Martin (doctoral student) and Sue Stephenson (field assistant) at Camp Finney (Nestor 2) during spring snow melt of the Mast River, La Pérouse Bay, Hudson Bay, Manitoba, Canada. Scan of Kodachrome Slide